An analytical method to calculate the settlement of reinforced piled embankment considering three-dimensional deformed geogrid. Issue 8 (11th June 2022) - Cui, Xiaoyan; Zhuang, Yan; Ning, Shuai; Wang, Kangyu
Abstract: The methods available to predict the strain and tension of geogrid are regularly based on two-dimensional condition, however, the three-dimensional deformed shape of geogrid is seldom considered in the literature. This paper proposed an analytical method to calculate the settlement of reinforced piled embankment considering three-dimensional deformed geogrid, in which the arching effect, the bearing capacity of geogrid and subsoil were taken into account. Firstly, three-dimensional deformation formula of geogrid was derived. Then the load transfer mechanism in the reinforced piled embankment was analyzed, including deriving the vertical stress at the base of the embankment, the vertical stress acting on the geogrid and that taken by the subsoil for piles arranged in the square pattern and in triangle pattern. The proposed analytical method can calculate the maximum settlement at the surface of the subsoil directly, and then the vertical stress acting on the subsoil surface, as well as the distribution of vertical stress along the embankment height can be derived. Finally, the proposed analytical method was used to calculate the settlement of two field cases. The difference between the results calculated from the proposed analytical method and the measurements was 19.5% and 9.2%, respectively, which validated the proposed analytical method.